1983
DOI: 10.1128/iai.42.1.333-340.1983
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a monoclonal antibody directed against type 1 fimbriae organelles from Escherichia coli

Abstract: We have isolated a mouse immunoglobulin M (IgM) monoclonal antibody directed against type 1 fimbriae from the Escherichia coli K-12-derived strain CSH50. Antibody specificity was demonstrated by (i) the ability of fimbriate but not nonfimbriate bacteria to compete with solid-phase purified fimbriae for antibody binding in an enzyme-linked immunosorbent assay, (ii) the visualized binding of antibody to fimbriae alone by electron microscopy, and (iii) the appearance in a radioimmunoprecipitation assay of a singe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Numerous studies have suggested that the various gene clusters have been lost during evolution as a pathoadaptive response to the host. Notably, laboratory growth methods consistently used to demonstrate fimbrial production in strains of E. coli (19, 20) were not successful for either lab strains and clinical isolates of Shigella (17, 18). Our control media analyses, in which the combination of glucose and bile salts were absent, confirmed many of these previous findings on the phenotypic level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have suggested that the various gene clusters have been lost during evolution as a pathoadaptive response to the host. Notably, laboratory growth methods consistently used to demonstrate fimbrial production in strains of E. coli (19, 20) were not successful for either lab strains and clinical isolates of Shigella (17, 18). Our control media analyses, in which the combination of glucose and bile salts were absent, confirmed many of these previous findings on the phenotypic level.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Shigella is thought to have lost the ability to produce “traditional” E. coli adherence factors as the bacteria adapted to an intracellular lifestyle (2) due to three main reasons. First, Shigella grown in standard laboratory media lack structures upon transmission electron microscopy (TEM) (17, 18), unlike some strains of E. coli in which adherence factors are thought to be constitutively expressed (19, 20). Second, examination of Shigella genomes deposited in GenBank reveals that almost all adherence gene clusters, such as type 1 fimbriae (10, 21) and curli (22), contain at least one annotated pseudogene that is crucial for either the adherence factor structure or the assembly process (17, 23, 24).…”
Section: Introductionmentioning
confidence: 99%
“…Chemicals and buffers. All reagents were as previously described (2,6) Antibodies. For the enzyme-linked immunosorbent assay (ELISA) inhibition assay, we used rabbit serum specific for type 1 fimbriae as previously described (2).…”
mentioning
confidence: 99%
“…For the enzyme-linked immunosorbent assay (ELISA) inhibition assay, we used rabbit serum specific for type 1 fimbriae as previously described (2). For immunoprecipitations, we used this serum, a monoclonal antibody (MAb) previously described (6), and monospecific rabbit anti-maltose-binding protein serum, kindly provided by Phil Bassford, Jr. (10). Rabbit antimouse serum was kindly provided by Judy Teale (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation